British art and the First World War, 1914-1924 - Fox, James 1982- (Cambridge University Press, 2015)
The First World War is usually believed to have had a catastrophic effect on British art, killing artists and movements, and creating a mood of belligerent philistinism around the nation. In this book, however, James Fox paints a very different picture of artistic life in wartime Britain. Drawing on a wide range of sources, he examines the cultural activities of largely forgotten individuals and institutions, as well as the press and the government, in order to shed new light on art's unusual role in a nation at war. He argues that the conflict's artistic consequences, though initially disruptive, were ultimately and enduringly productive. He reveals how the war effort helped forge a much closer relationship between the British public and their art - a relationship that informed the country's cultural agenda well into the 1920s
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1900-2000; Geschichte 1914-1924; Geschichte; Gesellschaft; Weltkrieg (1914-1918); Art, British / 20th century / Themes, motives; World War, 1914-1918 / Art and the war; World War, 1914-1918 / Social aspects / Great Britain; Art and society / Great Britain / History / 20th century; Erster Weltkrieg; Kunst; Großbritannien; Great Britain / Intellectual life / 20th century